Incidence and Outcomes of Infections Caused by Multidrug-Resistant Enterobacteriaceae in Children, 2007–2015 - Meropol, Sharon B (J Pediatric Infect Dis Soc, 2018)
BACKGROUND: The escalating incidence of invasive disease caused by multidrug-resistant Gram-negative enteric Enterobacteriaceae (MDR-GNE) is a global concern. Scant published studies in which the epidemiology of these infections in children is described exist; previous studies focused mainly on adults, described circumscribed populations, or lacked clinical detail. The objective of this study was to examine and describe the incidence, risk factors, and outcomes associated with MDR-GNE infection in children. METHODS: In this cohort study, we used data from 48 children’s hospitals maintained by the Pediatric Health Information System. We documented the proportion of MDR-GNE diagnoses among children’s hospital patients aged 0 to <18 years who were diagnosed with an Enterobacteriaceae-associated infection between January 1, 2007, and March 31, 2015, and we analyzed the association between MDR-GNE infection and hospital length of stay and death before discharge. RESULTS: During the study period, 107610 discharges included a diagnosis code for Enterobacteriaceae infection, 724 (0.7%) of which included MDR-GNE infection. The incidence of MDR-GNE, and the proportion of infections with Enterobacteriaceae organisms that were MDR-GNE increased over the study period; from 0.2% in 2007 to 1.5% by 2015 (test for trend < .001). Almost one-quarter (23%) of the infections in children hospitalized for MDR-GNE were nosocomial. Increased odds of MDR-GNE infection were associated with older age and comorbid illnesses. Lengths of stay in patients with MDR-GNE infection were increased 20% (95% confidence interval, 9.9%–30.5%; P < .001) over those without MDR-GNE infection; the increased odds for death did not reach statistical significance (1.46 [95% confidence interval, 0.98–2.18]; P = .06). Results were robust to sensitivity analyses. CONCLUSIONS: The incidence of pediatric MDR-GNE infection increased during 2007–2015. MDR-GNE infection was associated with increased length of stay, and we found a trend toward increased risk of death. Infections with Gram-negative enteric bacilli are becoming increasingly difficult to treat; considering the global burden of these antimicrobial-resistant organisms, interventions to curtail or even reverse this trend are needed urgently.